Practitioner’s involvement in teaching & learning for quantity surveying course: student’s perspective - Zolkafli @ Zulkifli, U.K.; Zakaria, N.; Othman, M.; Harun, A.F. (2013)
The quantity surveying academic program in Malaysia’s public university is distinctive in that it is taught with sufficient contribution of practitioners in the form of academic input but still very low of contribution from practitioner as an instructor or teaching staff. This study is intended to get feedback on the practitioner based teaching model for the Quantity Surveying course focusing the scope in University of Malaya only. The aim is achieved by identify the needs of practitioner’s involvement in teaching and learning and by gathering views from students on the involvement of practitioner in teaching and learning. Quantitative method was adopted in this study. Questionnaires were distributed to all quantity surveying students in University Malaya. Finding shows that there is a need of practitioner input in teaching and learning in Quantity Surveying Course and the involvement from the practitioner is going to offer a potential model for developing the performance role of Quantity Surveyor in practice area.